P-014 Beyond diagnostic angiography: the transradial approach as first line for both anterior and posterior circulation interventions. (23rd July 2017) - Caplan, J; Snelling, B; Sur, S; Khandelwal, P; Starke, R; Yavagal, D; Peterson, E
Abstract : Introduction: Transradial access (TRA) has become standard of care for cardiac interventions given its improved safety over transfemoral access (TFA). Like many advances in interventional cardiology, adoption in neurointervention has lagged behind. At our center we have been using TRA routinely for diagnostic angiography and posterior circulation interventions. We recently expanded this "Radial First" philosophy to include all interventional procedures, with an emphasis on anterior circulation interventions. In this study we report our favorable experience using TRA in 74 consecutive patients undergoing interventional procedures, the majority of which were anterior circulation procedures. Methods: Our prospectively maintained database was retrospectively reviewed for patients from our institution who underwent neurointerventions from August 2015 to March 2017. Patients undergoing an interventional procedure where TRA was either used or attempted were included in this study. Diagnostic angiography was excluded. Operative reports were reviewed for patient demographics, clinical and procedural details. Results: A total of 74 patients met the inclusion criteria with an average age of 64.4 years (±17.8 years). Transradial access was used for anterior circulation pathology in 77% (n=57) of the cases. The targeted vessel was successfully reached in 90.5% (n=67) of all cases. The majority of the cases were performed for aneurysm treatment (27%, n=20) or acute ischemic stroke (33.8%, n=25). Other interventions performed included treatment of AVMS and dAVF, tumor embolization, angioplasty, balloon test occlusion, prolonged infusions and vessel sacrifice (see table). Seven of the cases represented a conversion from a failed attempt at TFA. Conversion to a transfemoral approach was required in 7 cases (9.5%). The right radial artery was used for 93% (n=69) of the cases. The average fluoroscopy time of all cases was 62.4 min (±37.9 min). The majority of cases used an 070 guide catheter, including flow diversion cases. A Simmons 2 shaped catheter was most frequently used to select the desired vessel off the aortic arch and then the 070 guide catheter was telescoped over the diagnostic catheter. There were no complications related to radial access. Conclusions: This represents the largest series of TRA for anterior circulation neurointerventional procedures. The targeted intervention was successfully performed via the radial approach in 91% of the cases, for a wide variety of pathologies, with no access-related complications. Given this technical success and improved access safety profile, we now employ the transradial approach as first line for interventional procedures. Disclosures: J. Caplan: None. B. Snelling: None. S. Sur: None. P. Khandelwal: None. R. Starke: None. D. Yavagal: 2; C; Medtronic. E. Peterson: 2; C; Codman, Stryker, Medtronic.